Allopreening in birds is associated with parental cooperation over offspring care and stable pair bonds across years - Kenny, E; Birkhead, T; Green, J (Oxford University Press, 2017)
Individuals of many species form bonds with their breeding partners, yet the mechanisms maintaining these bonds are poorly understood. In birds, allopreening is a conspicuous feature of interactions between breeding partners and has been hypothesized to play a role in strengthening and maintaining pair bonds within and across breeding attempts. Many avian species, however, do not allopreen and the relationship between allopreening and pair bonding across species remains unexplored. In a comparative analysis of allopreening and pair bond behavior, we found that allopreening between breeding partners was more common among species where parents cooperate to rear offspring. The occurrence of allopreening was also associated with an increased likelihood that partners would remain together over successive breeding seasons. However, there was no strong evidence for an association between allopreening and sexual fidelity within seasons or time spent together outside the breeding season. Allopreening between partners was also no more common in colonial or cooperatively breeding species than in solitary species. Analyses of evolutionary transitions indicated that allopreening evolved from an ancestral state of either high parental cooperation or high partner retention, and we discuss possible explanations for this. Overall, our results are consistent with an important role for allopreening in the maintenance of avian pair bonds.